2020
DOI: 10.1186/s13044-020-0075-z
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional and prospective study on anti-Müllerian hormone changes in a cohort of pre-menopausal women with a history of differentiated thyroid cancer

Abstract: Background: Anti-Müllerian hormone (AMH) decreases acutely after post-surgical radioactive iodine (RAI) ablation in females with differentiated thyroid cancer (DTC). Aim: We performed a cross-sectional and prospective study on AMH levels in pre-menopausal females with a history of DTC. Methods: Fifty-nine females after surgery and RAI (group 1) and 30 females after surgery alone (group 2) were studied. The control group consisted of 141 healthy women (group 3). The prospective study was performed in 43 and 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
0
10
1
Order By: Relevance
“…They found that AMH levels were only negatively correlated with age in the treatment group (rS -0.58; p = 0.0003) and in the control group (rS -0.81 p < 0.0001). Mittica et al performed a cross-sectional study comparing 59 women who underwent surgery and RAI for DTC, 30 women only receiving surgery and 141 healthy women (23). In this study, the main factor for lower AMH levels was also age and not the type of treatment.…”
Section: Rai Treatment and Ovarian Functionmentioning
confidence: 77%
See 1 more Smart Citation
“…They found that AMH levels were only negatively correlated with age in the treatment group (rS -0.58; p = 0.0003) and in the control group (rS -0.81 p < 0.0001). Mittica et al performed a cross-sectional study comparing 59 women who underwent surgery and RAI for DTC, 30 women only receiving surgery and 141 healthy women (23). In this study, the main factor for lower AMH levels was also age and not the type of treatment.…”
Section: Rai Treatment and Ovarian Functionmentioning
confidence: 77%
“…Seven studies examined the effect of RAI treatment on the ovarian reserve by assessing AMH levels after RAI treatment (Table 3) (9)(10)(11)(12)(13)22,23). Yaisch et al studied 30 women with DTC whom received RAI doses ranging from 1110 to 5550 MBq (30 to 150 mCi) after recombinant human thyrotropin stimulation.…”
Section: Rai Treatment and Ovarian Functionmentioning
confidence: 99%
“…Several studies have shown that, in certain complications associated with pregnancy, such as gestational diabetes or pre-eclampsia, there is an increase in oxidative stress. Faced with this situation, the body responds by enhancing its antioxidant mechanisms, some of which lie in the diet [ 156 , 157 ]. Selenium deficiency is also associated with an increased risk of miscarriage.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Mittica et al observed a non-significant reduction in AMH on ANOVA testing in women treated with RAI and in women after thyroidectomy. However, on applying Wilcoxon’s paired test, AMH significantly decreased between the first and second evaluations only in women treated with RAI, with no significant variations observed between the first and second determination in groups after thyroidectomy ( 22 ).…”
Section: Discussionmentioning
confidence: 95%